2021
DOI: 10.3390/agronomy11112364
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Technique for Classifying Bird Damage to Rapeseed Plants Based on a Deep Learning Algorithm

Abstract: Estimation of crop damage plays a vital role in the management of fields in the agriculture sector. An accurate measure of it provides key guidance to support agricultural decision-making systems. The objective of the study was to propose a novel technique for classifying damaged crops based on a state-of-the-art deep learning algorithm. To this end, a dataset of rapeseed field images was gathered from the field after birds’ attacks. The dataset consisted of three classes including undamaged, partially damaged… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Compared with the previous two oil tea cultivar recognition models, the overall accuracy and kappa coefficient of ResNet50 is higher, reaching 83.94% and 0.80. The ResNet50 also obtained better experimental results than the VGG16 model in the study of cultivar recognition of chrysanthemum and classification of rapeseed image [45,46]. This may be related to the greater number of hidden layers and the skip-connection structure in the ResNet50 model [47].However, for Ganshi 83-4, Changlin 53, Ganshi 84-8, and Gan 447, the InceptionV3, VGG16 and ResNet50 failed to recognize them accurately.…”
Section: Comparison and Analysis Of Cultivar Recognition Resultsmentioning
confidence: 97%
“…Compared with the previous two oil tea cultivar recognition models, the overall accuracy and kappa coefficient of ResNet50 is higher, reaching 83.94% and 0.80. The ResNet50 also obtained better experimental results than the VGG16 model in the study of cultivar recognition of chrysanthemum and classification of rapeseed image [45,46]. This may be related to the greater number of hidden layers and the skip-connection structure in the ResNet50 model [47].However, for Ganshi 83-4, Changlin 53, Ganshi 84-8, and Gan 447, the InceptionV3, VGG16 and ResNet50 failed to recognize them accurately.…”
Section: Comparison and Analysis Of Cultivar Recognition Resultsmentioning
confidence: 97%
“…The amount of data in this experiment was also limited, and the training results are likely to exhibit overfitting. To solve this problem, we adopted the transfer learning method to improve model generalization [40]. We used the backbone of the COCO dataset to pre-train the network model and used the trained backbone to train the wildlife dataset.…”
Section: Pre-trainingmentioning
confidence: 99%
“…In our opinion, such adaptive systems have a serious drawback, they cannot be customized to the individual characteristics of each root crop. In digital agriculture [10,11], computer vision systems are used to quickly detect and count plants [12][13][14][15], to determine their ripeness and diseases [16][17][18][19][20], as part of systems to protect against weeds and pests [21,22], to determine the position of cattle [23]. In recent years publications have shown that the problem of identifying diseased or mechanically damaged fetuses on transportation systems such as conveyor belts, drums, turbines and etc.…”
Section: Introductionmentioning
confidence: 99%